La communauté luthérienne de Lyon au XVIIIe siècle - Alain Briand-Barralon (Chrétiens et Sociétés, 2009)
A small Lutheran, native community especially of Germany, exists from the 16th century in Lyon. It benefits from a Church, settled in Geneva, from 1707. It is especially about traders, who go to Geneva four times a year for the Last Supper. But, from 1770, when the Calvinists of Lyon have finally a minister, Lutherans participate more and more in the Reformed Church of Lyon and leave Geneva.